1998
DOI: 10.1046/j.1464-410x.1998.0810s3024.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term use and tapered dose reduction of intranasal desmopressin in the treatment of enuretic children

Abstract: Objective To determine the time taken to achieve comwith no relapses, remaining dry with no further treatment, 7% achieved dryness after relapses during plete dryness, the management of desmopressin dosage to reduce the relapse rate, the mean dosage in those or after therapy, 7% improved (no more than two wet nights per week) and 15% did not respond to therapy responding and any side eCects of long-term treatment. Patients and methods Enuretic children (155, 68% boys or improved only slightly (>2 wet nights pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 12 publications
2
25
0
9
Order By: Relevance
“…In Moffatt's review of randomized clinical studies using desmopressin therapy, nearly all studies demonstrated a statistically significant reduction in wet nights [6]. Moreover, studies have demonstrated that desmopressin was effective at rapidly reducing bedwetting in a variety of doses and forms [7,8,9]. In our study, intranasal desmopressin provided an effective and well-tolerated means of providing control in children with nocturnal enuresis.…”
Section: Discussionsupporting
confidence: 49%
“…In Moffatt's review of randomized clinical studies using desmopressin therapy, nearly all studies demonstrated a statistically significant reduction in wet nights [6]. Moreover, studies have demonstrated that desmopressin was effective at rapidly reducing bedwetting in a variety of doses and forms [7,8,9]. In our study, intranasal desmopressin provided an effective and well-tolerated means of providing control in children with nocturnal enuresis.…”
Section: Discussionsupporting
confidence: 49%
“…Discontinuation of desmopressin at 3 months might have led to prompt relapse. Since the start of our study, reports of long-term treatment with desmopressin for up to 1 or 2 years have shown long-lasting remission rates [21,28]. Secondly, some of our patients may have subclinical dysfunctional voiding, although this did not manifest as daytime urinary symptoms, as noted by Yeung et al [27].…”
Section: Discussionmentioning
confidence: 52%
“…Vorzeitige Auslassversuche sind meist sinnlos und re sultieren in einer hohen Rückfallquote. Bei korrekter Dosierung und Anwendung liegt die Erfolgs rate bei 70% [18,19].…”
Section: Desmopressinunclassified